A real-world retrospective study of omeprazole-domperidone combination in managing acid peptic disease with PRoton-pump Inhibitors in patients with type 2 DiabEtes mellitus (PRIDE-2) - Bharat Saboo; Nimmi Mulwani; Anup Uttam Petare; Krishna Chaitanya Veligandla; Colette Stephen Pinto; Amey Mane; Rahul Rathod; Bhavesh Kotak (BioExcel Publishing Ltd, 2023)
Background: Proton-pump inhibitors, along with a prokinetic agent, are widely used to provide symptomatic relief amongst patients with acid peptic disease (APD). This article evaluates the effectiveness and safety of the omeprazole-domperidone combination amongst patients with type 2 diabetes mellitus for the management of APD. Methods: PRIDE-2 (PRoton-pump Inhibitor in patients with type 2 DiabEtes mellitus) is a retrospective study reviewing electronic medical records of patients with type 2 diabetes mellitus and APD who were receiving the omeprazole-domperidone combination and visiting multiple Indian healthcare settings between March 2018 and April 2021. The effectiveness outcome of the therapy was evaluated in terms of resolution of APD symptoms at visit 5 (120 days after baseline visit) compared with visit 1 (baseline visit). Safety was determined in terms of reported adverse events (AEs) during the treatment period (120 days). Results: A total of 174 patients were included in the study. The mean age of the patients was 51.5±9.6 years, with the majority (59.8%) being men. A significant proportion of patients reported relief from APD symptoms, including abdominal pain (91.6%), epigastric burning (68.7%), nausea (89.5%), flatulence (100.0%), loss of appetite (93.6%), and altered bowel movements (94.7%) (p<0.001 for each) at visit 5 compared with visit 1. No serious AEs were reported. Conclusion: Omeprazole-domperidone combination was beneficial in providing symptomatic relief to patients with diabetes and APD. The combination therapy was well tolerated, with few reports of minor AEs.